Innovations and frontiers in neonatology - Herting, Egbert; Kiess, Wieland 1958- (Basel : Karger, 2020)
Innovations and Frontiers in Neonatology provides up-to-date information for clinicians and scientists interested in perinatal medicine. Neonatal transition, neonatal medicine from a global perspective, aspects of care including nutrition, respiratory and temperature management, resuscitation, family-centered approaches, and problems of the term newborn are covered as are complications and long-term consequences of preterm birth. Should we ventilate and how? What are the lifelong consequences of being born too small? How can we protect the neonatal brain? Can we actively influence the microbiome? Can we achieve individualized medicine with the help of metabolomics, for example? Are stem cells the miracle cure? These are just a few of the questions that world experts cover in this book while, at the same time, they take a look at the future of neonatal medicine.
Keywords: NEONATOLOGÍA